THE NECESSITY OF IMPLEMENTING SMART CLASSROOMS IN THE TRAINING OF FUTURE INFORMATICS TEACHERS - Salgozha, I.T.; Turashova, Sh.P.; Seiduali, K.; Amangeldin, A.A. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
The article discusses the need to introduce smart classrooms into the educational process and their impact on the training of informatics teachers. Modern trends in educational technologies are analyzed, the importance of smart classrooms as a means of improving the effectiveness of teaching and organizing the learning space is emphasized. Special attention is paid to the training of teachers to work in such conditions, including the necessary qualifications, skills and methodological approaches. The article presents examples of successful practices, as well as discusses the challenges and difficulties that educational institutions may face when integrating smart classrooms. The article also describes an experimental study that substantiates the need to introduce smart classrooms into the educational process of training future informatics teachers.